Analisis Quality Of Service (QoS) pada Jaringan VPN dan MPLS VPN Menggunakan GNS3 - Mardianto, Mardianto (Jurnal Sains dan Informatika, 2019)
The ever-increasing internet is an ISP challenge for the future of the expected global computer network traffic and QoS needs. To maintain competitive ISPs in Indonesia with the development of internet usage, the demand for QoS must be increased. MPLS VPN networks combine layer 2 switching technology with layer 3 routing technology. MPLS VPN networks have emerged as technologies that meet VPN requirements such as private IP, and the ability to support overlapping addresses in resolving speed and QoS problems. The method used is experimental research. From the measurement results obtained by VPN and MPLS VPN network delay has a very good delay value. For throughput on VPN networks have medium quality and MPLS VPN networks have good quality. And for the packet loss value for both types of networks is 0%. This shows that MPLS VPN network throughput has better QoS while for delay and packet loss on VPN and MPLS VPN networks have the same quality value.